THE RELATIONSHIP BETWEEN ORAL HEALTH AND DEPRESSIVE SYMPTOMS IN LATER-LIFE. (11th November 2018) - Lee, H; Lee, Y; Lee, D; Hwang, M; Lee, H; Ley, C
Abstract: A growing number of studies started to address the link between oral health and subjective well-being of older adults such as depressive symptoms. Yet, there is a limited knowledge on exploring this relationship based a population- based longitudinal data. To examine how various oral health conditions relate to depressive symptoms, this study uses regression models focusing on older Americans aged 51 and older from the Health and Retirement Study (2008–2010). The result indicated oral health conditions such as higher levels of gum sensitivity is associated with higher levels of depressive symptoms. Stratified by gender, the results showed that for men, higher levels of food avoidance was associated with greater levels of depressive symptoms whereas, for women, higher levels of gum sensitivity was associated with higher levels of depressive symptoms. Geriatric health professionals can utilize oral health improvement interventions to enhance the psychological well-being of older adults.